Comparative Explorations Of Human-Poultry Relationships, Pandemic Preparedness and the Search for Viral Epicentres (Medicine Anthropology Theory, 2021)
In this book review, I compare three timely ethnographies that critically explore the topics of human–poultry relationships, avian influenza, and global health. I start the review by considering how the three authors, each located in a different context, approach these topics by drawing upon distinct methodological and theoretical frameworks. I then show how these approaches shape the way in which the authors discuss three separate concepts: preparedness, experiments, and viruses. I conclude that, whether read independently or together, these books illustrate the power of ethnographic research in exposing the distinctive ways that people envisage the relationships between human and non-human lives and the implications of such distinctions for disease control.